Pelargonidin improves functional recovery and attenuates neuropathic pain following spinal cord injury in rats: relevance to its neuroprotective, antioxidant, and anti-inflammatory effects - Kooshki, Leila; Fakhri, Sajad; Abbaszadeh, Fatemeh; Kiani, Amir; Farzaei, Mohammad Hosein; Mohammadi-Noori, Ehsan; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundSpinal cord injury (SCI) significantly impairs individuals’ sensorimotor functions, hindering daily activities. Current therapeutic options often demonstrate limited efficacy and lead to undesirable side effects. Emerging research highlights the potential of anthocyanins, especially pelargonidin, which possess neuroprotective, anti-inflammatory, and antioxidant properties beneficial for neurological conditions.PurposeThis study sought to explore the impact of intrathecal administration of pelargonidin on the recovery of sensory-motor functions and associated disorders in a rat model of SCI through neuroprotective effects and regulating inflammatory/oxidative stress mediators.Materials and methodsIn total, 35 male Wistar rats were divided into five groups: sham, SCI, and three treatment groups receiving different intrathecal concentrations of pelargonidin (1, 2, and 4 mM) once on day 0 after surgery/injury. Weight changes were assessed and behavioral analyses were done, including hot plate tests, acetone drop tests, von Frey tests, inclined plane tests, as well as Basso, Beattie, and Bresnahan (BBB) scores, weekly up to day 28 post-injury. On day 28, serum levels of nitrite, catalase, and glutathione as well as matrix metalloproteinase (MMP) assays and histological evaluations were done.Results and discussionPelargonidin significantly attenuated neuropathic pain, improved motor performance, and reduced weight loss in rats with SCI. Biochemical assays demonstrated increased serum catalase/glutathione level, and MMP2 activity, while decreased serum nitrite level and MMP9 activity. Histological analyses showed an enhancement in the number of motor neurons in the ventral horn of the spinal cord after treatment with pelargonidin, highlighting its neuroprotective and neurogenic effects.ConclusionPelargonidin makes substantial therapeutic benefits following SCI by accelerating sensorimotor recovery. This effect is likely due to its strong antioxidant, anti-inflammatory, and neuroprotective properties.